PENGUATAN EDUWISATA MANGROVE BERKELANJUTAN DI DESA PENGUDANG, KECAMATAN TELUK SEBONG, KABUPATEN BINTAN - Andriyono, Sapto; Wahyudi, Irfan; Maradona, Maradona; Kinasih, Sri Endah; Hamida, Layli; Santoso, Yuniawan Heru; Saputra, Hijrah; Pangestu, Chandra Trisna (Jurnal Abdi Insani, 2025)
Pengudang Village in Teluk Sebong District, Bintan Regency, has a well-preserved and diverse mangrove ecosystem that has strategic potential to be developed as a community-based ecotourism destination. Current management remains limited to recreational aspects, while the educational value and contribution to the local economy have not been fully optimized. This community service program aimed to strengthen the development of mangrove educational tourism by enhancing community capacity, providing educational facilities, and encouraging innovation of products based on coastal resources. The method involved a needs assessment through questionnaires, interviews, and focus group discussions, which served as the basis for designing a training curriculum. The curriculum consisted of modules on mangrove and seagrass ecology, English for tourism, and seaweed-based product processing, supported by learning media such as field guidebooks, posters, and dialogue materials. The results showed an increase in community knowledge of the ecological functions of mangroves, which were previously perceived only as “coastal trees” but are now understood comprehensively as providing coastal protection, serving as carbon sinks, and offering habitats for aquatic biota. Simulation-based English training improved tourism communication skills, despite some pronunciation difficulties, while the integration of digital technology, including the use of ChatGPT, enhanced the learning process. Seaweed processing training resulted in the development of an innovative seaweed pie, a distinctive culinary product with promising economic potential. High community participation, particularly among young people, became an important social asset for program sustainability. The program demonstrated that integrating ecological, educational, and creative economic aspects could strengthen Pengudang Village as a model for sustainable mangrove-based educational tourism development.